On The Edge Irregularity Strength of Firecracker Graphs F2,m - Ramdani, Rismawati; Suwandi, Desi Laswati (KUBIK: Jurnal Publikasi Ilmiah Matematika, 2022)
Let Â be a graph and k be a positive integer. A vertex k-labeling Â is called an edge irregular labeling if there are no two edges with the same weight, where the weight of an edge uv is . The edge irregularity strength of G, denoted by es(G), is the minimum k such that Â has an edge irregular k-labeling. This labeling was introduced by Ahmad, Al-Mushayt, and BacË‡a in 2014.Â An (n,k)-firecracker is a graph obtained by the concatenation of n k-stars by linking one leaf from each. In this paper, we determine the edge irregularity strength of fireworks graphs F2,m.